Why elections fail - Norris, Pippa (Cambridge University Press, 2015)
Too often, elections around the globe are, unfortunately, deeply flawed or even fail. What triggers these problems? In this second volume of her trilogy on electoral integrity, Pippa Norris compares structural, international, and institutional accounts as alternative perspectives to explain why elections fail to meet international standards. The book argues that rules preventing political actors from manipulating electoral governance are needed to secure integrity, although at the same time officials also need sufficient resources and capacities to manage elections effectively. Drawing on new evidence, the study determines the most effective types of strategies for strengthening the quality of electoral governance around the world. With a global perspective, this book provides fresh insights into these major issues at the heart of the study of elections and voting behavior, comparative politics, democracy and democratization, political culture, democratic governance, public policymaking, development, international relations and conflict studies, and processes of regime change.